ANALISIS PENGARUH CORPORATE SOCIAL RESPONSIBILITY, DAN EARNINGS MANAGEMENT TERHADAP PERFORMA KINERJA PERUSAHAAN DENGAN UKURAN PERUSAHAAN SEBAGAI VARIABEL MODERASI (Studi Empiris pada Perusahaan Sektor Industri Barang Konsumsi yang Terdaftar di Bursa Efek Indonesia Tahun 2017-2019) - Annisa Aulia Rahma; Imam Ghozali (Diponegoro Journal of Accounting, 2021)
The purpose of this research is to examine the effect of the relationship between corporate social responsibility, earnings management, and firm performance, and the impact of firm size on the association between corporate social responsibility, earnings management, and firm performance in the fast-moving consumer goods industry. The variables used in this research are corporate social responsibility and earnings management as independent variables as well as firm performance as the dependent variables. Furthermore, this research will use firm size as moderating variable. The samples of this research are fast-moving consumer goods companies listed on the Indonesian Stock Exchange from 2017 to 2019 with total sample is 135 samples. The data used in this research is secondary data which was obtained through the purposive sampling method. The analytical technique used for examining the hypothesis is through multiple linear regressions. The result of this research shows that CSR has a positive impact on firm performance. Earnings management has a negative significant effect on firm performance. The firm size managed to moderate and provide a significantly positive effect to strengthen the relations between CSR and firm performance. Meanwhile, the firm size is also able to moderate, giving the effect of strengthening the relationship of earnings management to the firm's performance.